Analisis Penerapan Metode Kaporitisasi Sederhana Terhadap Kualitas Bakteriologis Air PMA. - Rohim, Miftahur; Nurjazuli, Nurjazuli; Joko, Tri (Jurnal Kesehatan Lingkungan Indonesia, 2006)
ABSTRACT Background: Water bacteriological quality is a parameter required for fresh water. The bacteriological content  is high because of the contamination from surrounding or activity of people near the area. From fact in the field, most of water bacteriological quality in Indonesia is still worse. In Flores land area, especially in Boawae the water from PMA are not treated by a good tretment water. Result of water quality monitoring program in Boawae, indicating that the MPN Coli Content is 210 Col/100 ml sample. One of the alternatives is to improve bacteriological quality is by using chlorination process of the PMA water. The aim of the study was to analyze the difference between physicchemist parameter and bacteriological parameter in PMA water after chlorinated by using three methods (Single Tube an Layered Tube and Molasses Tube). Methods: The research was experimental research with one group and after intervention design. Number of sample is 270: 30 samples of PMA water control, 120 samples before treatment and 120 samples after the treatment. The physicochemist sample and bacteriological sample has examinate according to examination procedure in laboratory. Data was analyzed by using method of univariate, bivariate and multivariate as Kruskal Wallis test and Cochran test. Results: The result of the research showed that from the treatment of a single tube, layered tube and molasses tube was found that there were  differences among parameters of pH, TDS, Chlor, Fe, Mn, NO2 , NO3 , CaCO3 , Coliform total, E.Coli with a 5%  p=0,0001. Conclusion : It is concluded that based on parameter of Chlor, Coliform total and E.Coli, the better and suitable devices of water  treatment is Layered Tube Key Words : Clean Water, Chlorination and Bacteriological